Preservation techniques and their effect on nutritional values and microbial population of brewer’s spent grain: a review - Geberemariyam Terefe (CABI Agriculture and Bioscience)
Abstract The most prevalent by-product produced by the brewery factory is brewer's spent grain (BSG). A total of 70%, 10%, and 20% of the BSG produced are used for animal feed, biogas production, and landfills, respectively. Feeding wet brewery spent grain can avoid the cost of drying. Wet brewery spent grain is used as a replacement for forage in the diets of animals. The high moisture content and ease of deterioration of wet brewery leftover grain as a fresh feed are drawbacks (3–5 days). BSG is provided as a low-cost feed despite its greater perishability and microbiological instability. There are two significant challenges brought on by the BSG's higher moisture content (80%). First, transportation is expensive. Second, the abundance of proteins and polysaccharides in BSG promotes microbial development and deterioration. Therefore, these problems can be solved by utilizing various preservation methods, including drying (solar, freeze, and oven drying), freezing, ensiling (both alone and in combination with other animal feeds), and additives (Silo-King GPX preservatives, xylanase, carbohydrase (econase) and protease (alcalase), urea and lime, sodium formate, calcium propionate, formic and propionic acids, acetic acid, NaCl, NaOH, HCl, and H2SO4).